Scaling‐up biodiversity‐ecosystem functioning research - Gonzalez, Andrew; Germain, Rachel M.; Srivastava, Diane S.; Filotas, Elise; Dee, Laura E.; Gravel, Dominique; Thompson, Patrick L.; Isbell, Forest; Wang, Shaopeng; Kéfi, Sonia; Montoya, Jose; Zelnik, Yuval R.; et al. (Ecology letters, 2020)
A rich body of knowledge links biodiversity to ecosystem functioning (BEF), but it is primarily focused on small scales. We review the current theory and identify six expectations for scale dependence in the BEF relationship: (1) a nonlinear change in the slope of the BEF relationship with spatial scale; (2) a scale‐dependent relationship between ecosystem stability and spatial extent; (3) coexistence within and among sites will result in a positive BEF relationship at larger scales; (4) temporal autocorrelation in environmental variability affects species turnover and thus the change in BEF slope with scale; (5) connectivity in metacommunities generates nonlinear BEF and stability relationships by affecting population  synchrony at local and regional scales; (6) spatial scaling in food web structure and diversity will generate scale dependence in ecosystem functioning. We suggest directions for synthesis that combine approaches in metaecosystem and metacommunity ecology and integrate cross‐scale feedbacks. Tests of this theory may combine remote sensing with a generation of networked experiments that assess effects at multiple scales. We also show how anthropogenic land cover change may alter the scaling of the BEF relationship. New research on the role of scale in BEF will guide policy linking the goals of managing biodiversity and ecosystems. We address the challenge of scale for biodiversity and ecosystem functioning (BEF) research. We review current theory and identify six expectations for scale dependence in the BEF relationship. We suggest directions for synthesis that combine theoretical and empirical methods and suggest their application to human transformed landscapes.